(untitled) (Journal of Asian Development Studies, 2025)
This study examines the dynamics of epistemic colonization and the process of decolonization in Uzma Aslam Khan’s The Miraculous True History of Nomi Ali. Drawing on Walter Mignolo’s theory of decoloniality, the study explores how colonial powers imposed language, religious ideologies, and Eurocentric knowledge systems to erase indigenous identities and cultures. The novel has been analysed as a site of resistance where subaltern voices challenge dominant narratives and reclaim their cultural and historical presence. The study finds that epistemic justice is central to the broader decolonial project, as Khan’s narrative critiques the colonial control over knowledge and its long-term psychological and cultural ramifications. The novel offers a compelling reconstruction of its historical background. It unearths neglected events and perspectives that have been suppressed in official colonial records. It further exposes the silenced histories of colonized individuals and shows how colonialism used knowledge and culture as tools of control and erasure. Through the portrayal of lived experiences under imperial rule, Khan emphasizes the resilience of indigenous epistemologies and the silent struggles of oppressed communities. This research contributes to postcolonial literary studies by highlighting the transformative role of decolonial frameworks in reshaping historical memory and resisting epistemic violence. Ultimately, the study affirms the significance of literature as a means of reclaiming truth, identity, and justice in the aftermath of colonial domination.